Purinergic receptors are a key bottleneck in tumor metabolic reprogramming: The prime suspect in cancer therapeutic resistance - Aria, Hamid; Rezaei, Marzieh; Nazem, Shima; Daraei, Abdolreza; Nikfar, Ghasem; Mansoori, Behnam; Bahmanyar, Maryam; Tavassoli, Alireza; Vakil, Mohammad Kazem; Mansoori, Yaser (Frontiers in Immunology, 2022)
ATP and other nucleoside phosphates have specific receptors named purinergic receptors. Purinergic receptors and ectonucleotidases regulate various signaling pathways that play a role in physiological and pathological processes. Extracellular ATP in the tumor microenvironment (TME) has a higher level than in normal tissues and plays a role in cancer cell growth, survival, angiogenesis, metastasis, and drug resistance. In this reviewstudy, we investigated the role of purinergic receptors in the development of resistance to therapy through changes in tumor cell metabolism. When a cell transforms to neoplasia, its metabolic processes change. The metabolic reprogramming modified metabolic feature of the TME, that can cause impeding immune surveillance and promote cancer growth. The purinergic receptors contribute to therapy resistance by modifying cancer cells' glucose, lipid, and amino acid metabolism. Limiting the energy supply of cancer cells is one approach to overcoming resistance. Glycolysis inhibitors which reduce intracellular ATP levels, may make cancer cells more susceptible to anti-cancer therapies. The loss of the P2X7R through glucose intolerance and decreased fatty acid metabolism reduces therapeutic resistance. Potential metabolic blockers that can be employed in combination with other therapies will aid in the discovery of new anti-cancer immunotherapy to overcome therapy resistance. Therefore, therapeutic interventions that are considered to inhibit cancer cell metabolism and purinergic receptors simultaneously can potentially reduce resistance to treatment.